Evaluation of differences in the performance strategies of top and bottom basketball teams utilizing rank-sum ratio comprehensive - Sun, Wenping; Chee, ChenSoon; Kok, LianYee; Lim, FongPeng; Samsudin, Shamsulariffin (Frontiers in Sports and Active Living, 2022)
This study carried out a rank-sum ratio (RSR) comprehensive evaluation analysis on the attack, defense, and overall attacking and defensive performance between the top and bottom teams during the 2019 Men's Basketball World Cup. The results showed that the attacking performance of the top eight teams was far better than the bottom eight teams in terms of average points, 2-point shoot percentage, 3-point shoot percentage, free throw percentage, turnovers, and assists, and there was a significant difference (p0.05). However, the second attack and fast-break showed no significant difference between the two cohorts (P > 0.05), and the offensive rebounds of the bottom eight teams were better than the top eight teams. Additionally, there was a large gap between the top eight teams and bottom eight teams in lost points and defensive rebounds, with a very significant difference (p0.01). However, steals, blocks, and fouls had no significant difference between the two cohorts (P > 0.05). Additionally, there was a very significant difference between the final ranking and attack, defense, and the overall attack-defense RSR (p0.01), and most top teams focused on developing both attack and defense and paid attention to improving the overall attacking and defensive ability. Moreover, there was a significant relationship between the overall attack-defense performance and assists, rebounds, turnovers, 2-point shoot percentage, defensive rebounds, fast-break points, blocks, and free throw percentage (P0.05). These results can provide a targeted reference for the future development of the teams, and also serve as valuable guidance for coaches and players in the training process.